Experimental and analytical investigations of reinforced concrete beams strengthened by different CFRP sheet schemes - Khaled Fawzy; Hilal Hassan; M. Madqour (Fracture and Structural Integrity)
The use of reinforced fibre polymers to strengthen and repair structural elements is widely spreading. However, there is lack of knowledge of the actual behavior of strengthened structures with FRP sheets. This paper discusses the experimental results of the flexural strengthening of reinforced concrete (RC) beams by carbon fibre-reinforced polymer (CFRP) sheets bonded by epoxy adhesive to the tensile surface of the beams. Using a four-point bending load system over an effective span of 1800 mm, a total of ten beams with an overall dimension of 150 mm * 200 mm * 2000 mm with different degrees of strengthening schemes were tested. The number of layers, strengthening scheme (side and U-shape bonding) and reinforcement ratio are the major parameters of the experimental study. The research indicates that the flexural strength of the beams was substantially improved as the layers of laminate increased (between 31.80 and 71.50 %) and using U shape in ends that delay or prevent debonding failure. The experimental results compared to that analytically obtained by using ANSYS model showing acceptable agreement with deviations varying no more than 10 % for all specimens.